2016
DOI: 10.3126/jpahs.v3i2.20273
|View full text |Cite
|
Sign up to set email alerts
|

Relaparotomy after caesarean section

Abstract: Introductions: Relaparotomy after caesarean section is rare and literature are scanty. The decision requires a good clinical judgment to save mother’s life. Our objective was to analyse the outcome of relaparotomy after caesarean section at Patan Hospital.Methods: This was a cross sectional study done at the department of obstetrics and gynaecology, Patan Hospital, Lalitpur, Nepal. Charts of the caesarean section from January 2010 to December 2014 were reviewed to analyze the cases of relaparotomy for incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…During 2 years of study, there were a total number of 16,901 deliveries among 10,478 cases by normal vaginal and 6423 cases by C-section delivery. Among 6423 cases 16 cases required relaparotomy and the incidence was found to be 0.25% which is similar to the other studies [1][2][3][4][5][6][7][8] . Placenta previa, Antepartum hemorrhage (APH), Dystocia, Malpresentation, Fetal distress, altered biophysical profile (BPP), and Premature rupture of membrane (PROM) were major indications for C-section with comorbidities such as fibroid uterus, severe pre-eclampsia, and anemia were associated with our study population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…During 2 years of study, there were a total number of 16,901 deliveries among 10,478 cases by normal vaginal and 6423 cases by C-section delivery. Among 6423 cases 16 cases required relaparotomy and the incidence was found to be 0.25% which is similar to the other studies [1][2][3][4][5][6][7][8] . Placenta previa, Antepartum hemorrhage (APH), Dystocia, Malpresentation, Fetal distress, altered biophysical profile (BPP), and Premature rupture of membrane (PROM) were major indications for C-section with comorbidities such as fibroid uterus, severe pre-eclampsia, and anemia were associated with our study population.…”
Section: Discussionsupporting
confidence: 87%
“…Many studies reported that hemorrhage was the leading indication for Relaparotomy after C-section. Hemoperitoneum was a major indication of relaparotomy in Raagab et al, Ahmed et al, and Levin et al studies [12,3,8] . Burst abdomen (31.25%) was the second most indication of relaparotomy in our study.…”
Section: Discussionmentioning
confidence: 98%
“…4 In present study, the caesarean delivery was 77.3% in oligohydramnios, much higher than average total caesarean delivery of 39.15% in a previous study done at Patan hospital claims. 12 The main limitations of our study was assessment of AFI on three different machines, and by different operators. Also, exclusion of twin pregnancies, not comparing the study group with the control group with normal AFI and not considering neonatal complications associated with borderline or low AFI.…”
Section: Resultsmentioning
confidence: 93%
“…81.8% which is in line with most of the previous studies. 4,6,7,8 Surgeries performed urgently and emergently had higher rates of morbidity and mortality compared to elective ones as shown in a study by Mullen et al which highlighted the need for improved risk stratification. 12 Lack of proper preoperative checkup, urgent need of delivery, changes in anatomy of the lower segment of uterus and bladder associated during advanced labor, lack of availability of adequate set of manpower and increased chances of sepsis are probably common causes of morbidity and mortality associated with emergency procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The major indications of relaparotomy are primary and secondary PPH, burst abdomen, slippage of ligature, rectus sheath hematoma and infections due to leak. 6,7,8 Due to significant morbidity and mortality associated with re-laparotomies, one should be very vigilant on measures during primary surgery to avoid it. Measures like proper pre-operative workup, proper light and exposure, newer antibiotics and proper antiseptics, better post-operative fluid and electrolyte balance, proper surgical techniques, secured hemostasis, complete exploration and appropriate drainage are the few among many which can reduce relaparotomies .9 This study will help to determine the factors and risk situations that are associated with relaparotomy in obstetrics practice so that they can be worked upon by all concerned departments as well as aid the obstetrician to be more vigilant and be cautious in the primary surgery to prevent the further secondary surgical intervention and its morbidities.…”
Section: Introductionmentioning
confidence: 99%